DESAIN SLIDE ADJUSTER KURSI TRUK MENGGUNAKAN METODE TRIZ - Choirul Anwar (Universitas 17 Agustus 1945 Jakarta, 2018)
The increasing competition in the selling price of the vehicle makes the OEM lot of cost reduction programs to obtain competitive prices. The OEM's main program is to provide handling of product design to production to suppliers. One of its products is the slide adjuster of truck seats. The difficulties encountered by local suppliers are complex design, lack of product knowledge and new players. In an effort to answer the challenge, the supplier uses TRIZ method to create the design concept. The results of the design concepts obtained can provide price reductions due to the results of function analysis can be done component reduction. The decision is based on the result of different component functions and patent study. For structural strength of the slide adjuster verification with CAE with maximal 357.4 MPa stopper strength in bracket lock. Rattle slide obtained maximum 2.775 mm y direction. Slide load obtained 82.5 N. TRIZ method can effectively be used to design slide truck seat adjuster products.